2020
DOI: 10.1097/mph.0000000000001961
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Use of Romiplostim for SARS-CoV-2–induced Thrombocytopenia

Abstract: The literature regarding coronavirus disease of 2019 (COVID-19) infection in pediatrics indicates that children have less severe clinical presentations and lower mortality rates. There remains limited data regarding hematologic sequelae in pediatric patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Romiplostim has shown a platelet response in pediatric patients with chronic immune thrombocytopenic purpura, and eltrombopag is proven to increase platelet counts in patients with inherite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Also, approaches combining JAK1/2 inhibitors with blockade of C5a with eculizumab are being considered as a treatment of severe pulmonary damage in COVID-19 patients [67]. Moreover, drugs such as romiplostim acting as an agonist for the thrombopoietin receptor are also predicted to be useful to treat COVID-19-associated thrombocytopenia, in agreement with a recent case study documenting platelet recovery following treatment with this drug of a COVID-19 pediatric patient [54].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Also, approaches combining JAK1/2 inhibitors with blockade of C5a with eculizumab are being considered as a treatment of severe pulmonary damage in COVID-19 patients [67]. Moreover, drugs such as romiplostim acting as an agonist for the thrombopoietin receptor are also predicted to be useful to treat COVID-19-associated thrombocytopenia, in agreement with a recent case study documenting platelet recovery following treatment with this drug of a COVID-19 pediatric patient [54].…”
Section: Discussionsupporting
confidence: 53%
“…The thrombopoietin receptor appears as well to be a valid therapeutic target for agonists in light of the high incidence of thrombocytopenia associated with COVID-19 infection [54]. Rather unexpectedly, Topoisomerase 1 inhibitors, currently used as cytotoxic drugs in…”
Section: Plos Onementioning
confidence: 99%
“…After screening by title and abstract, 246 articles proceeded to full-text review. Following full-text review, 126 articles, which reported on a total of 48,332 patients, were included for data extraction and analysis 25–148. The PRIMSA flow diagram is provided in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Several additional prospective trials are ongoing to evaluate romiplostim for the treatment of CIT in patients with non-hematologic cancers (phase 2; NCT02052882), gastrointestinal or colorectal cancer (phase 3; NCT03362177), and NSCLC, ovarian cancer, or breast cancer (phase 3; NCT03937154). Although there is little evidence regarding optimal management strategies for thrombocytopenia in the setting of COVID-19, two recent cases have been reported of patients with acute thrombocytopenia secondary to COVID-19 successfully treated with romiplostim (81,82). A 67-year-old male patient developed severe thrombocytopenia complicated by subdural hematoma and rectal bleed, associated with COVID-19.…”
Section: Romiplostimmentioning
confidence: 99%
“…The second patient was a 6-year-old male with a complex m edical history, including m ild chronic thrombocytopenia. Following a further reduction in platelet count that was associated with SARS-CoV-2 infection, he received romiplostim to stimulate platelet production, which resulted in the resolution of spontaneous bleeding and improvement of platelet counts (82). Based on these (albeit limited) findings, it is feasible that the use of romiplostim may also be of benefit in preventing or treating acute thrombocytopenia in patients receiving myelosuppressive chemotherapy in a COVID-19/post-COVID-19 setting, including those with existing COVID-19 infection.…”
Section: Romiplostimmentioning
confidence: 99%